2013
DOI: 10.1001/jamasurgery.2013.414
|View full text |Cite
|
Sign up to set email alerts
|

An Emergency Department Thawed Plasma Protocol for Severely Injured Patients

Abstract: Objectives To expedite delivery and transfusion of plasma through implementation of an emergency department (TP-ED) protocol. Design Retrospective cohort study Setting ACS-verified level 1 trauma center Patients Protocol was initiated February 2010, placing four units of AB plasma in the ED. All trauma patients admitted eight months before (TP-BB) and after implementing the TP-ED protocol. Patients were included if they received at least one unit of RBC and one unit of plasma in the first six hours after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 24 publications
(31 reference statements)
4
66
0
4
Order By: Relevance
“…59,60 This notion was further corroborated by Rawdan and colleagues, who reported that moving thawed plasma from the blood bank to the emergency department, enabling early balanced blood product transfusion, was associated with a reduction in overall blood product use and a 60% decrease in odds of 30-day mortality. 61 These studies all suggest that rapid infusion of balanced blood products into bleeding patients is critical to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 This notion was further corroborated by Rawdan and colleagues, who reported that moving thawed plasma from the blood bank to the emergency department, enabling early balanced blood product transfusion, was associated with a reduction in overall blood product use and a 60% decrease in odds of 30-day mortality. 61 These studies all suggest that rapid infusion of balanced blood products into bleeding patients is critical to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, we moved thawed plasma from the blood bank to the emergency department because it was taking up to 40 minutes to infuse plasma into patients. 11 We now have 4 units of RBCs and 4 units of liquid AB plasma in our emergency department, which are available for rapid infusion as the primary resuscitative fluid. Infusion times of plasma are now within 3 minutes of patient arrival.…”
mentioning
confidence: 99%
“…In one study, having a "1:1:1" protocol resulted in earlier use of FFP, but the FFP:PRBC ratio at 24 hours was identical to that before "1:1:1" implementation; and mortality and blood products use decreased [18]. Other centers have documented increased survival and/or reduced blood product use after implementation of "1:1:1" [19][20][21][22][23][24][25][26][27][28]. There is conflicting data on FFP wastage.…”
Section: The Controversymentioning
confidence: 99%